Evaluación de conductas anormales y estereotipias en equinos de una escuela de equitación de la ciudad de Loja. - Jaramillo Rodríguez, Josselyn Milena (2024)
Equines that remain in prolonged confinement are prone to developing abnormal and stereotyped behaviors due to the lack of animal welfare, which leads to economic losses. The objective of this study was to evaluate the abnormal and stereotyped behaviors in equines of a riding school in the city of Loja. Twenty-six animals stabled between 15 and 20 hours per day were studied. A camera trap was used for 24-hour individual evaluations. The behaviors observed were recorded in an ethogram, where frequency and duration were measured. Of the evaluated horses, 7 (26.92%) exhibited abnormal behaviors or stereotypies. Six horses showed crib-biting with a very high relative frequency, reaching up to 464 occurrences per day, and wind sucking varying between 11 to 51 times per day, considered moderate and high, representing an average percentage of time per day of 1.02 and 0.52, respectively. Pawing was observed in 5 horses, with an absolute frequency between 17 and 52 times per day, considered very high. Three horses exhibited box-walking, with a relative frequency ranging from moderate to high, and an absolute frequency between 15 and 47 times per day. One animal exhibited weaving, with a duration of up to 20 seconds per event and a high relative frequency. Nodding exhibited a high relative frequency, and bed-eating behavior had a moderate relative frequency, with a maximum duration of 25 seconds per event, both behaviors observed in 2 equines. In conclusion, the equines of the riding school in the city of Loja exhibited abnormal and stereotyped behaviors, among which the most frequent were crib-biting, wind sucking, box- walking, bed eating, and pawing.